Distribution and Clustering of Cutaneous T-Cell Lymphoma (CTCL) Cases in Canada During 1992 to 2010. Issue 2 (March 2018) - Ghazawi, Feras M.; Netchiporouk, Elena; Rahme, Elham; Tsang, Matthew; Moreau, Linda; Glassman, Steven; Provost, Nathalie; Gilbert, Martin; Jean, Sara-Elizabeth; Roshdy, Osama; Pehr, Kevin; Sasseville, Denis; et al.
Background: Clustering of patients with cutaneous T-cell lymphoma (CTCL) was reported in several jurisdictions around the world. This rare cancer is known to affect spouses and in some cases multiple members of the same family. These combined results suggest the existence of external disease triggers/promoters. We recently conducted the first comprehensive analysis of CTCL incidence and mortality in Canada, which revealed case clustering in several regions. Objectives: To extend our previous analysis on CTCL incidence across Canada and to provide all the collected data on CTCL patient incidence in Canada during the period of 1992 to 2010. Methods: Clinical parameters for patients with CTCL in Canada were analyzed using 2 independent population-based cancer registries: Canadian Cancer Registry and Le Registre Québécois du Cancer. The CTCL incidence rates were examined on different geographical levels, including provinces/territories, cities, and forward sortation areas. Results: Our findings further corroborate our earlier observations of higher CTCL incidence in Newfoundland and Labrador, maritime provinces (Nova Scotia and New Brunswick), and prairie provinces (Manitoba and Saskatchewan). Also, most cities with high CTCL incidence were located in these provinces. Extensive mapping of high-incidence postal codes supports case clustering in a number of communities that are located in the proximity of industrial centres and seaports. Conclusions: Detailed analysis of CTCL incidence in Canada is critical to fully understand the burden of this disease in our country, to begin the search for a possible external trigger for this lymphoma, and to reform how health care resources are distributed throughout the country to better serve Canadian patients with CTCL.